ОСНОВЫ ИДЕОГРАФИЧЕСКОГО ОПИСАНИЯ СОМАТИЧЕСКИХ (на материале романа З.Сәмәди «Истәк вә қисмәт») - Курванбакиева, А. Н. (Journal of Oriental Studies, 2016)
Novel З. The "Fate and desire" of Samadhi is the last ofnovels in its creativity. Consideration of somaticphraselogical units represents rich material for studying ofoutlook of the Uyghur nations. The analysis of given unitspromoted revealing of communication of somaticphraseological units with the person, its ability to live.Белгілі ұйғыр жазушысы З.Самадидің «Тілек пенжазмыш» атты романы оның соңғы шығармасы болыптабылады.Бұл мақала адамның дүниетанымынан, оның ішкірухани дүниесінен көріністер беретін соматикалықфразеологизмдерді қарастыруға арналған.